Patulin and patulin producing Penicillium spp. occurrence in apples and apple-based products including baby food - Walid Hammami; Roda Al-Thani; Stefano Fiori; Saeed Al-Meer; Fathy Atia Atia; Duha Rabah; Quirico Migheli; Samir Jaoua (Journal of Infection in Developing Countries)
Introduction: Patulin has raised the international attention because of its health risk. In fact, it has mutagenic, neurotoxic, immunotoxic, genotoxic and gastrointestinal effects in animals. In the present work, patulin and patulin-producing Penicillium spp. in apple and apple-based products marketed in Qatar were analysed. Methodology: Sampling was carried out using apple fruits and apple-based products. Fungi were isolated from undamaged apples, apple juice and baby apple food. DNA extraction was carried out with DNeasy Plant Mini Kit (QIAGEN, Valencia, USA). The molecular identification of fungal isolates was carried out using ITS1-ITS4 PCR. PCR products were sequenced and blasted. Patulin was extracted and analyzed by LC/MS/MS, then quantified using Agilent 1290UHPLC coupled to 6460 triple quadruple mass spectrometer. Results: Forty-five samples of undamaged fresh apple fruits, apple juice and apple-based baby food products sold in different markets in Qatar were surveyed for both fungal and patulin contamination using Liquid Chromatography Tandem Mass Spectrometery (LC/MS/MS). Twenty-five Penicillium spp. isolates were selected, including 23 P. expansum and one isolate each of P. brevicompactum and P. commune. All the tested Penicillium spp. isolates produced patulin in vitro (from 40 to 100 μg/g on Malt Yeast Extract agar medium). Patulin was detected in 100% of apple juice samples at levels ranging from 5.27 to 82.21 µg/kg. Only 5 samples contained patulin levels higher than European Union recommended limit (50 µg/kg). The average patulin contamination was 30.67 µg/kg and 10.92 µg/kg in baby apple juice and in baby apple compote, respectively.